IMPLEMENTATION OF KINDERGARTEN CHILDREN’S GUIDANCE SERVICES BASED ON ACTIVE PLAY IN PHYSICAL EDUCATION AND DIGITAL TECHNOLOGY - Dwi Adhinda Junaidi Putri; Tawakal (CV. Naskah Aceh, 2026)
This community service activity aims to implement a guidance service model for kindergarten children through active play based on physical education and supported by digital technology at TK IT Peusijuk Hate. This program was initiated due to the limited integration of guidance services, physical activity, and technology in early childhood education. The implementation employed training and mentoring approaches for teachers, combined with active play activities designed according to children’s developmental needs. Data were collected through observation, interviews, and documentation. The results indicate that the implementation of active play-based guidance services supported by digital media improves children’s social-emotional development, participation, and self-regulation. In addition, teachers at TK IT Peusijuk Hate showed increased competence in integrating guidance principles into physical education activities. In conclusion, the program effectively strengthens guidance services for kindergarten children through the integration of physical activity and digital technology.